A vision and neural network based air-ground coordinated control system - Muyun Jiang; Jiahui Shi; Hongbin Ma; You Li (ICUS : proceedings of 2017 IEEE International Conference on Unmanned Systems : October 27-29, 2017, Beijing, China, 2017)
This paper presents an air-ground coordinated system made up of an Unmanned Aerial Vehicle (UAV) and an Unmanned Ground Vehicle (UGV). The movement of UGV is totally controlled by UAV and multiple sensors are adopted in the system to ensure the stability. A novel neutral network algorithm is introduced to identify the location and orientation of UGV. Each component is introduced and tested in detail and the coordinated system performs a satisfying result.